(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article analyzes the role of fiscal policy in managing aggregate demand and stabilizing the economy. The article explains how fiscal policy affects economic growth and inflation, and the impact of government spending and taxes on aggregate demand using graphs. The effectiveness of current fiscal mechanisms and their future prospects are also discussed.